Sootnošenie nagruzok raznoj napravlennosti i adaptacija organizma v makrocikle podgotovki plovcov vysokoj kvalifikacii - Širkovec, E. A.; Kvašuk, P. V.; Šustin, B. N. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The increase in sports results in swimming is usually associated not only with the implementation of large volumes of specialized loads, but also with a significant intensification of training activities. When exceeding the optimal level of loads and reducing the recovery rate, the intensity of the training should be dynamically adjusted. The study of the mechanisms of formation of a set of qualities that reflect the dynamics of adaptation of organism systems is a necessary prerequisite for effective management of the process of training of highly qualified swimmers.